2014
DOI: 10.1002/nau.22679
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of urinary incontinence and its association with multimorbidity in women aged 50 years or older: A population‐based study

Abstract: The prevalence of UI was high. Mixed incontinence was the most frequent type of UI. Many associated factors can be prevented or improved. Thus, health policies targeted at these combined factors could reduce their prevalence rate and possibly decrease the prevalence of UI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
48
0
20

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 39 publications
9
48
0
20
Order By: Relevance
“…Verificou-se outra importante associação neste estudo: entre a autopercepção negativa do estado de saúde e a prevalência de IU nas idosas. Na literatura, pesquisas também apresentam esse resultado 7,26 . A perda involuntária de urina pode causar isolamento social, alterações no sono e na sexualidade 27 .…”
Section: ▄ Resultadosunclassified
See 1 more Smart Citation
“…Verificou-se outra importante associação neste estudo: entre a autopercepção negativa do estado de saúde e a prevalência de IU nas idosas. Na literatura, pesquisas também apresentam esse resultado 7,26 . A perda involuntária de urina pode causar isolamento social, alterações no sono e na sexualidade 27 .…”
Section: ▄ Resultadosunclassified
“…Atenção especial deve ser dada ao idoso que não avalia positivamente sua condição de saúde, almejando um melhor manejo das condições crônicas e das incapacidades para promover qualidade de vida e aumento da longevidade 31 . De maneira similar a este trabalho, outros estudos também encontraram associação entre a IU e o relato de artrite, artrose e reumatismo entre as mulheres idosas 26,32 . A osteoartrose é descrita como a doença articular mais comum, especialmente entre indivíduos idosos 33 .…”
Section: ▄ Resultadosunclassified
“…Reigota et al [14] evaluated the possible risk factors of UI including hypertension and they found that UI was higher in women with HT. The association between hypertension and UI was investigated in several studies and most of them emphasized on the possible side effects of medical treatments of HT especially diuretics, betablockers, or alpha-adrenoreceptor blocking agents [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Age is considered the main risk factor for female UI, with prevalence of 52.3% among Brazilian women over 50 years of age (2). In Turkey, the average age of the highest UI prevalence was 48.7 years (18) and in Portugal only 11.5% of the women under 39 years of age had UI (19).…”
Section: Discussionmentioning
confidence: 99%
“…Defined as any involuntary loss of urine (1), Urinary Incontinence (UI) is a frequent condition, with an estimated prevalence of 52.3% in Brazilian women (2) and having projected costs amounting to US $ 82.6 billion in 2020 in the United States (3). The UI symptoms lead to different problems such as psychological changes and disturbances in personal, sexual, social and professional relationships, negatively influencing the quality of life of this population (4).…”
Section: Introductionmentioning
confidence: 99%